2017
DOI: 10.3354/meps12315
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic right whale foraging ecology and its role in human-caused mortality

Abstract: Endangered North Atlantic right whales Eubalaena glacialis suffer from unacceptably high rates of ship strikes and fishing gear entanglements, but little is known of the role that diving and foraging behavior plays in mediating human-caused mortality. We conducted a study of right whale foraging ecology by attaching tags to whales for short periods of time (hours), tracking their movements during daytime, and repeatedly sampling oceanographic conditions and prey distribution along the whales' tracks. Right wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…The data presented here support the findings by Baumgartner et al (2017) that right whales dive to the seafloor in most study areas. In that study, the authors found that 15 of the 55 tagged whales dove to within 0 to 10 m of the seafloor and they did so in 5 out of the 6 study sites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data presented here support the findings by Baumgartner et al (2017) that right whales dive to the seafloor in most study areas. In that study, the authors found that 15 of the 55 tagged whales dove to within 0 to 10 m of the seafloor and they did so in 5 out of the 6 study sites.…”
Section: Discussionsupporting
confidence: 91%
“…These concentrations primarily occur near the sur-face, just above the bottom mixed layer (approximately 50−75 m above the seafloor), or as close as 5 m off the seafloor. Baumgartner et al (2017) found nearly one-quarter of the 55 whales tagged dove to the seafloor and they did so in all but one habitat. Most, but not all, of those whales appeared to be feeding near the seafloor.…”
Section: Introductionmentioning
confidence: 93%
“…Irrespective of these errors, pseudo tracks do, however, capture the qualitative nature of animal movement and can be useful in inferring how animals move, rather than where they go; for our purpose, these tracks illustrate the degree to which right whales move horizontally within dives (Figure ). The variation in the horizontal movement patterns of whales foraging at depth (Figure ) as well as small‐scale changes in the vertical dimension between dives (Figure S3) further suggest that right whales are capable of detecting fine‐scale variations in prey density and adjusting their foraging behaviour accordingly (Baumgartner et al, ; Kenney, Mayo, & Winn, ; Mayo & Goldman, ; Mayo & Marx, ). Simultaneous measurements of the vertical distribution of prey and right whale diving behaviour made in foraging habitats have shown how right whales are able to repeatedly target the depth of maximum copepod concentrations (Baumgartner & Mate, ; Parks et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesized that if whales were consistently diving to their aerobic dive limit, they would have filtered lower total volumes of water in deeper dives, due to the time required to transit to the foraging patch (Thompson & Fedak, ). However, the lack of a significant effect of dive depth on the total volume filtered per dive and the low explanatory power of depth on foraging duration emphasizes that by completing many shorter, aerobic dives with steep ascents and descents and short surface intervals right whales maximize the time spent foraging in a consistent prey patch, regardless of its depth (Baumgartner et al, ). While individuals are able to optimize their time foraging in high‐density prey layers, they apparently will also go without foraging for extended periods of time (2+ hr; Figure S1) in this otherwise rich environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation